Bunionectomy as an Acute Postoperative Pain Model: Overview of Common Experimental Methods, and Insights from Past Clinical Trials - Singla N; Rogier T; Meske DS (Journal of Pain Research)
Neil Singla,1 Timothy Rogier,2 Diana S Meske3 1Lotus Clinical Research, New Providence, NJ, USA; 2Independent Consultant, Los Angeles, CA, USA; 3Chariton Pharmaceuticals, Cambridge, MA, USACorrespondence: Neil Singla, Email nsingla@lotuscro.comAbstract: To obtain broad regulatory approval for a new analgesic agent in acute postoperative pain, US and European regulatory authorities require pivotal studies in both hard (bony) tissue pain and soft tissue pain. Bunionectomy is by far the most common hard tissue pivotal trial model, in spite of the fact that the model has limited relevance to clinicians prescribing pain drugs (pain from bunionectomy is not extreme or long-lasting, and is adequately treated by existing drugs). The authors outline the experimental characteristics that make bunionectomy an appealing study model for researchers despite its lack of clinical relevance compared to larger surgeries. These include bunionectomy’s high signal-to-noise ratio (secondary to the ability to standardize surgical procedures, anesthesia and perioperative care) and relative operational simplicity (including relatively easy subject enrollment). They present an overview of the surgical and anesthetic protocols typical to modern bunionectomy studies, as well as common design paradigms, common endpoints, and other key design features of bunionectomy trials. They also provide an informal qualitative review of bunionectomy acute pain studies performed in the past 15 years, and a master table of acute pain bunionectomy trials performed from 2006– 2023. Drawing from their informal review of past studies, the authors discuss trends in rescue medication, study enrollment rates, subject demographics, and the advantages and disadvantages of bunionectomy compared with another common acute pain model, dental impaction pain (third molar extraction).Keywords: bunionectomy, acute pain clinical trials, acute postoperative pain